The effects of initial soil moisture conditions on swale flow hydrographs. Issue 5 (12th February 2018) - Rujner, Hendrik; Leonhardt, Günther; Marsalek, Jiri; Perttu, Anna‐Maria; Viklander, Maria
Abstract: The effects of soil water content (SWC) on the formation of run‐off in grass swales draining into a storm sewer system were studied in two 30‐m test swales with trapezoidal cross sections. Swale 1 was built in a loamy fine‐sand soil, on a slope of 1.5%, and Swale 2 was built in a sandy loam soil, on a slope of 0.7%. In experimental runs, the swales were irrigated with 2 flow rates reproducing run‐off from block rainfalls with intensities approximately corresponding to 2‐month and 3‐year events. Run‐off experiments were conducted for initial SWC ( SWC ini ) ranging from 0.18 to 0.43 m 3 /m 3 . For low SWC ini, the run‐off volume was greatly reduced by up to 82%, but at high SWC ini, the volume reduction was as low as 15%. The relative swale flow volume reductions decreased with increasing SWCini and, for the conditions studied, indicated a transition of the dominating swale functions from run‐off dissipation to conveyance. Run‐off flow peaks were reduced proportionally to the flow volume reductions, in the range from 4% to 55%. The swale outflow hydrograph lag times varied from 5 to 15 min, with the high values corresponding to low SWC ini . Analysis of swale inflow/outflow hydrographs for high SWC ini allowed estimations of the saturated hydraulic conductivities as 3.27 and 4.84 cm/hr in Swales 1 and 2, respectively. Such estimates differed from averages ( N  = 9) of double‐ring infiltrometer measurements (9.41 and 1.78 cm/hr). Irregularities in swale bottom slopes created bottom surface depression storage of 0.35 and 0.61 m 3 for Swales 1 and 2, respectively, and functioned similarly as check berms contributing to run‐off attenuation. The experimental findings offer implications for drainage swale planning and design: (a) SWC ini strongly affect swale functioning in run‐off dissipation and conveyance during the early phase of run‐off, which is particularly important for design storms and their antecedent moisture conditions, and (b) concerning the longevity of swale operation, Swale 1 remains fully functional even after almost 60 years of operation, as judged from its attractive appearance, good infiltration rates (3.27 cm/hr), and high flow capacity.